Replication of a Nipah Virus Encoding a Nuclear-Retained Matrix Protein. (30th October 2019) - Ringel, Marc; Behner, Laura; Heiner, Anja; Sauerhering, Lucie; Maisner, Andrea
Abstract: Nipah virus (NiV) matrix protein (NiV M) plays a major role in virus assembly. It undergoes nuclear transit before accumulating at the plasma membrane and recruiting nucleocapsids to the budding sites. Because nuclear NiV M cannot be detected in all cell types, we wondered whether it can reach the cell surface by bypassing the nucleus. Using an M mutant with a defective nuclear export signal (MNESmut ), however, we revealed that the nuclear import of M is ubiquitous, because MNESmut was retained in the nuclei of all cell types tested. Because a functional nuclear transit is a general prerequisite for M surface transport, we wanted to characterize the effect of nuclear-retained M protein in a full viral context and generated a recombinant NiV-MNESmut . Mutant NiV-MNESmut caused increased cell-cell fusion and produced lower virus titers. As expected for an assembly defective NiV, perinuclear inclusions (IBperi ) were formed, but inclusions at the plasma membrane (IB PM ), which probably represent the viral assembly platforms, were not found. It is interesting to note that the transport-defective MNESmut was recruited to IBperi . This probably prevents overaccumulation of nonfunctional M proteins in the cytoplasm and nuclei of NiV-infected cells and thus provides first evidence that IBperi are functionally relevant aggresome-like compartments.